2019
DOI: 10.1080/15384101.2019.1568747
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: miR-506 contributes to malignancy of cutaneous squamous cell carcinoma via targeting of P65 and LAMC1

Abstract: Previous research has shown that microRNA 506 (miR-506) functions as an essential modulator in the development of many biological reactions, including multiple cancers. However, its involvement in cutaneous squamous cell carcinoma (CSCC) has been rarely reported. In the present work, we investigated the molecular mechanism and function of miR-506 in the regulation of CSCC cell viability and metastasis (migration and invasion). We observed that miR-506 expression was upregulated in both CSCC tissues and cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Similarly, in cSCC, some miRNAs expressions have been reported to be dysregulated and play crucial roles in tumorigenesis and development in cSCC. For instance, Zhou et al demonstrated that miR-506 expression was upregulated in both cSCC tissues and cell lines and downregulation of miR-506 expression repressed tumorigenesis in cSCC cells by targeting P65 and LAMC1 [ 20 ]. The miR-217 expression, which was upregulated in the cSCC cell lines and was found to promote cSCC cell growth, cell cycle and invasion, contributed to the development of cSCC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in cSCC, some miRNAs expressions have been reported to be dysregulated and play crucial roles in tumorigenesis and development in cSCC. For instance, Zhou et al demonstrated that miR-506 expression was upregulated in both cSCC tissues and cell lines and downregulation of miR-506 expression repressed tumorigenesis in cSCC cells by targeting P65 and LAMC1 [ 20 ]. The miR-217 expression, which was upregulated in the cSCC cell lines and was found to promote cSCC cell growth, cell cycle and invasion, contributed to the development of cSCC [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang et al, LAMC1 overexpression indicates poor prognosis in hepatocellular carcinoma (HCC)[ 33 ]. LAMC1 overexpression also indicated poor prognosis for cutaneous squamous cell carcinoma[ 34 ] and prostate cancer[ 35 ]. LAMC1 may participate in HCC progression by regulating PKM2 expression via the PTEN/AKT pathway[ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gong et al [47] reported that miR-221 promotes cell proliferation and colony growth by repressing PTEN. Furthermore, it was shown that inhibition of miR-506 induces apoptosis and decreases invasion and migration of cSCC cell lines [49]. In this study, LAMC1 and p65 were identified as direct targets of miR-506.…”
Section: Mirnas In Cutaneous Squamous Cell Carcinomamentioning
confidence: 65%
“…Functional analyses show that miR-365 inhibits apoptosis by directly targeting BAX [44] and forcing the cell cycle progression by NFIB repression [42, 43]. As shown in recent studies, miR-186, miR-221, miR-506, and miR-142-5p contribute to cSCC tumor growth [45-49]. miR-186 promotes proliferation and inhibits apoptosis by targeting RETREG1 [48] and APAF1 [46].…”
Section: Mirnas In Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%